2017
DOI: 10.1016/j.bone.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Use of dual energy X-ray absorptiometry in pediatric patients

Abstract: Dual Energy X-ray Absorptiometry (DXA) is a vital tool for assessing bone health in patients at risk for fragility fractures. In pediatric patients, this technology is used in conjunction with clinical fracture history to diagnosis osteoporosis and monitor treatment response. Childhood and adolescence is characterized by linear growth and bone mass accrual; thus there are important differences in the interpretation of bone measurements obtained by DXA in these young patients. This review aims to explore the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 95 publications
(116 reference statements)
1
58
0
Order By: Relevance
“…We adjusted BMD z-scores for height in patients aged 4 to 20 years using the method described by Zemel et al, 29 which has been shown to be least biased for age and height-for-age compared with other methods. 26,29,34,35 Low BMD was defined as >1 SD (z-score less than −1) and very low BMD as >2 SDs (z-score less than −2) below age-matched, sex-matched, and race-matched norms, consistent with prior studies in childhood cancer survivors. 13,[36][37][38][39][40]…”
Section: Bmd Evaluationmentioning
confidence: 88%
See 2 more Smart Citations
“…We adjusted BMD z-scores for height in patients aged 4 to 20 years using the method described by Zemel et al, 29 which has been shown to be least biased for age and height-for-age compared with other methods. 26,29,34,35 Low BMD was defined as >1 SD (z-score less than −1) and very low BMD as >2 SDs (z-score less than −2) below age-matched, sex-matched, and race-matched norms, consistent with prior studies in childhood cancer survivors. 13,[36][37][38][39][40]…”
Section: Bmd Evaluationmentioning
confidence: 88%
“…52 Also, our definition of low BMD is consistent with prior studies by others in survivors. 23,26,27,29,[31][32][33][34][35][36][37][38][39][40]53 An important consideration is the clinical implications of identifying reduced BMD. The COG long-term follow-up guidelines recommend survivors with/at risk of decreased BMD conduct regular weight-bearing activity and ensure adequate vitamin D/calcium intake through diet or supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DXA is a two‐dimensional projection technique that summarizes total bone mass within the projected bone area. This measurement of areal BMD (grams per square centimeter) is known to systematically underestimate volumetric BMD (grams per cubic centimeter) in children with poor growth, and various methods have been used to adjust for body size . In light of this intrinsic limitation of DXA analysis and the fact that in our study cohort we observed a strong correlation between DXA measurements and anthropometrics (Table ), we elected to adjust for height and weight using the method of Short et al Although the ALGS and CIC participants were similar with respect to weight, height, and BMI Z scores, only the ALGS group showed a significant normalization of DXA Z scores after anthropometric adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is usually diagnosed by measuring bone mineral density (BMD) of the spine or femur. Dual energy X-ray absorptiometry (DXA) is recommended for precise diagnosis of low bone mass [8][9][10][11] . No DXA equipment is currently available in Laos.…”
Section: Introductionmentioning
confidence: 99%